Caption presentation method and apparatus using same (2005)
A caption presentation method and an apparatus using the method, by which caption and information related to the caption can be provided together in a broadcast receiver or in an image reproducer that displays the caption in a closed caption method. The method includes detecting subject information from a caption signal; obtaining visual information with respect to the caption, based on the detected caption subject information; and displaying the visual information and the caption signal together.